The potential of mRNA vaccine in HCC treatment - Rui Han (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2023)
Neoantigen mRNA vaccines are a potential form of immunotherapy for Hepatocellular Carcinoma (HCC). These neoantigens can be targeted with personalized mRNA vaccines, which are designed to stimulate the patient's immune system to recognize and destroy cancer cells. Neoantigen mRNA vaccines are developed using RNA sequences that are synthesized based on the genetic mutations found in HCC patients. These RNA sequences are formulated into a vaccine and administered to the patient, typically in combination with other cancer treatments for enhancing the anti-cancer effect. Several preclinical and clinical studies have shown promising results for neoantigen mRNA vaccines in HCC immunotherapy. Early results suggest that they may be a valuable addition to the treatment options available for HCC patients. However, more research is needed to determine the safety and efficacy of these vaccines.